Research on carbon emissions of urban residents' three types of dining based on the whole life cycle. (22nd August 2022) - Zhao, Zimo; Lv, Xiuyuan; Wang, Yuanhao; Lv, Guangfeng; Miao, Bo; Hu, Qing; Ouyang, Cheng; Liu, Yukun; Yan, Luhui
Abstract: Following the promulgation and implementation of China's 'carbon peak' and 'carbon neutrality' policies, the evaluation of the carbon footprint of the domestic catering industry is particularly important. Currently, comparative studies on the life-cycle carbon footprint of different common dining styles, such as home cooking, restaurant dining and takeaway, are scarce. Focused on three dining methods, this paper involved in-depth research on carbon footprint of the whole life cycle from the perspectives of whole industry and specific dish. The carbon footprint contribution of each stage of three different dining ways is obtained from the four stages, namely, the stage of upstream raw materials and manufactures, the stage of platform empowerment, the stage of consumer dining and the stage of waste treatment. The study found that the carbon emissions of the three dining ways in the overall industry analysis were canteen (2.9564 kgCO2 e/per person) > takeaway (2.4821 kgCO2 e/per person) > home cooking (2.2778 kgCO2 e/per person); and the carbon emissions of honey sauce fork-fired were canteen (6.5843 kgCO2 e/per person) > home cooking (6.4721 kgCO2 e/per person) > takeaway (5.6718 kgCO2 e/per person). The production of raw materials and products is the largest stage of carbon emissions among the three dining ways. Besides the carbon emissions of raw materials, the storage and cooking of food products are the unit processes with large carbon emissions. According to the results of sensitivity analysis, traffic travel mode is an important factor affecting the carbon footprint of canteen food. The above research can provide effective basis and data support for policy formulation.